2003
DOI: 10.1523/jneurosci.23-18-07227.2003
|View full text |Cite
|
Sign up to set email alerts
|

KCNQ/M Currents in Sensory Neurons: Significance for Pain Therapy

Abstract: Neuronal hyperexcitability is a feature of epilepsy and both inflammatory and neuropathic pain. M currents [IK(M)] play a key role in regulating neuronal excitability, and mutations in neuronal KCNQ2/3 subunits, the molecular correlates of IK(M), have previously been linked to benign familial neonatal epilepsy. Here, we demonstrate that KCNQ/M channels are also present in nociceptive sensory systems. IK(M) was identified, on the basis of biophysical and pharmacological properties, in cultured neurons isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
396
4
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 335 publications
(433 citation statements)
references
References 47 publications
21
396
4
2
Order By: Relevance
“…1. Two voltagedependent exponential time constants were required to fit the deactivation of the M-current, in agreement with previous measurements (12,17), and neither their amplitudes nor their voltage-dependences are affected by expression of either fusion protein (Fig. 2 D and E).…”
Section: Expression Of a Cam-binding Fusion Protein Decreases The Neusupporting
confidence: 87%
“…1. Two voltagedependent exponential time constants were required to fit the deactivation of the M-current, in agreement with previous measurements (12,17), and neither their amplitudes nor their voltage-dependences are affected by expression of either fusion protein (Fig. 2 D and E).…”
Section: Expression Of a Cam-binding Fusion Protein Decreases The Neusupporting
confidence: 87%
“…First, it inhibits a potassium current carried by Kv7.2/Kv7.3 channels, the so-called M-current; this causes the cells to depolarize and to fire more action potentials when challenged with a depolarizing current - i.e., they are more excitable. This itself is not that unexpected (though not previously shown in sensory neurons), since the M-current had already been identified in nociceptive sensory neurons (6), and the authors (7) and others (8) have previously shown that M-current inhibition is the cause of the excitatory action of bradykinin on sympathetic neurons. However, the second effect is new: the authors report that the rise in Ca 2+ concentration also activates a calciumdependent chloride current.…”
Section: Patwardhan Et Al In This Issue Of the Jci Identifies Oxidizsupporting
confidence: 59%
“…The pharmacology of this particular channel type has already started to be investigated as the channel might also be of interest in neuropathic pain, 48 epilepsy 49,50 and to improve memory. 42 …”
Section: Pp2a-bc and Kcnq2 In Bipolar Diseasementioning
confidence: 99%